2021
DOI: 10.1371/journal.pone.0246433
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of nitrogen and phosphorus accumulation and their stoichiometry along a chronosequence of forest primary succession in the Hailuogou Glacier retreat area, eastern Tibetan Plateau

Abstract: As the two limiting nutrients for plants in most terrestrial ecosystems, nitrogen (N) and phosphorus (P) are essential for the development of succession forests. Vegetation N:P stoichiometry is a useful tool for detecting nutrient limitation. In the present work, chronosequence analysis was employed to research N and P accumulation dynamics and their stoichiometry during forest primary succession in a glacier retreat area on the Tibetan Plateau. Our results showed that: (1) total ecosystem N and P pools increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Previous research on biologically relevant elements in the Hailuogou region focused on the change in C, N and P mass ratios and stocks (e.g., Bing et al 2016b;He and Tang 2008;Wu et al 2015;Yang et al 2021;Zhang et al 2021;Zhou et al 2013) or contamination by trace metals (e.g. Bing et al 2016aBing et al , 2019Luo et al 2015;Wang et al 2020).…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research on biologically relevant elements in the Hailuogou region focused on the change in C, N and P mass ratios and stocks (e.g., Bing et al 2016b;He and Tang 2008;Wu et al 2015;Yang et al 2021;Zhang et al 2021;Zhou et al 2013) or contamination by trace metals (e.g. Bing et al 2016aBing et al , 2019Luo et al 2015;Wang et al 2020).…”
Section: Study Areamentioning
confidence: 99%
“…Zhou et al (2016b) reported that weathering processes in the Hailuogou are initially dominated by the weathering of carbonates followed by a more intense biogeochemical weathering (>80 yr) because of lower pH values. In a recent study, Yang et al (2021) suggested that N is the main growth-limiting element in the Hailuogou area based on N:P stoichiometric ratios in leaves. Wang et al (2021) recently reported a positive effect of pioneer N 2 -fixing plants on the establishment of other non-N 2 -fixing species after glacier retreat.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The acceleration of glacier melting caused by global warming in recent years has created bare land in different periods which can be accurately measured, providing ideal places to study the primary succession of vegetation [ 27 , 28 , 29 ]. Most studies on vegetation succession in glacial retreat areas focus on the vegetation composition and structure, soil nutrient status and the coupling relationship of plant-soil-microbial interactions [ 30 , 31 , 32 , 33 ]. However, the N utilization strategies of dominant plants at different stages of primary succession are poorly understood, and therefore, the patterns and mechanisms for plants adjusting their N preference to adapt to environmental changes remain to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…ese elements can a ect the physical energy cycle and terrestrial ecosystem balance [1]. Over the past few years, numerous studies have reported spatial variations and in uencing factors for soil N/P chemometric characteristics in terrestrial ecosystems [2,3]. A typical study is Cambardella et al [4].…”
Section: Introductionmentioning
confidence: 99%